Update on protease‐activated receptor 2 in cutaneous barrier, differentiation, tumorigenesis and pigmentation, and its role in related dermatologic diseases. Issue 8 (15th May 2019) - Henehan, Mason; De Benedetto, Anna
Abstract: Protease‐activated receptor 2 (PAR2) is a transmembrane receptor expressed by multiple tissues, including skin, with rapidly expanding knowledge regarding its roles. In the skin, PAR2 has extensively documented effects in promoting Th2 inflammation and pruritus; and its role in atopic dermatitis continues to be thoroughly studied. Numerous new investigations have shown a more complex range of activities potentially related to dermatologic diseases. Goal of this review is to outline emerging effects of PAR2 activation in the skin other than those related to immunologic and pruritic functions. Specifically, this work seeks to summarize current knowledge (and gaps) of PAR2 as a regulator of epidermal barrier, keratinocyte differentiation, cutaneous tumorigenesis and pigmentation. Additional focus will be placed on possible involvement in dermatologic disease and emergence as a therapeutic target.